Social Support and Academic Burnout among University Students Living in an Islamic Boarding School in Pekanbaru, Indonesia - Ainun Salsya Agfirlila; Muhammad Jais; Wilasari Arien (Program Studi Pendidikan Masyarakat, 2026)
University students who live in Islamic boarding schools simultaneously face academic demands and structured religious-residential obligations, which may increase vulnerability to academic burnout. This study examined the level of perceived social support and academic burnout and tested whether social support was associated with lower academic burnout among university santri at the Miftahul Huda Student Islamic Boarding School in Pekanbaru, Indonesia. A quantitative ex post facto, cross-sectional design was used. From a population of 135 students, 101 respondents were selected through simple random sampling. Data were collected between October 2025 and January 2026 using researcher-developed five-point questionnaires. Following a 30-person pilot test, the social-support instrument retained 39 items and the academic-burnout instrument retained 37 items; both showed very high internal consistency (Cronbach’s alpha = .988). Perceived social support had a mean score of 3.33, whereas academic burnout had a mean score of 3.78. Emotional support was the highest-rated support dimension (M = 3.36), while low academic self-confidence was the highest burnout indicator (M = 3.80). Simple linear regression showed that social support was negatively associated with academic burnout (B = -1.300, SE = .225, t = -5.767, p < .001), explaining 25.1% of the variance in burnout (R² = .251; adjusted R² = .244). The findings indicate that social support is a meaningful protective resource but is insufficient on its own; prevention strategies should also address workload, time management, self-efficacy, recovery, and coordination between academic and boarding-school responsibilities.